2017
DOI: 10.1111/pbi.12689
|View full text |Cite
|
Sign up to set email alerts
|

A single point mutation in Ms44 results in dominant male sterility and improves nitrogen use efficiency in maize

Abstract: SummaryApplication of nitrogen fertilizer in the past 50 years has resulted in significant increases in crop yields. However, loss of nitrogen from crop fields has been associated with negative impacts on the environment. Developing maize hybrids with improved nitrogen use efficiency is a cost‐effective strategy for increasing yield sustainably. We report that a dominant male‐sterile mutant Ms44 encodes a lipid transfer protein which is expressed specifically in the tapetum. A single amino acid change from ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 40 publications
(52 reference statements)
3
82
0
Order By: Relevance
“…However, it is difficult to explain how Ms44 could elicit a change in plant growth rate. Male sterility, caused by Ms44 , is the result of a single‐nucleotide polymorphism (SNP) causing an error in the splicing of the targeting peptide of a lipid transfer protein expressed exclusively in the tapetum for a short period of time after tetrad release (Fox et al, 2017). It is inconceivable how this gene function could be associated with an increase in whole‐plant growth rate or biomass.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is difficult to explain how Ms44 could elicit a change in plant growth rate. Male sterility, caused by Ms44 , is the result of a single‐nucleotide polymorphism (SNP) causing an error in the splicing of the targeting peptide of a lipid transfer protein expressed exclusively in the tapetum for a short period of time after tetrad release (Fox et al, 2017). It is inconceivable how this gene function could be associated with an increase in whole‐plant growth rate or biomass.…”
Section: Resultsmentioning
confidence: 99%
“…Deployment of GMS hybrid technology through a blended hybrid is feasible through the use of a maintainer inbred line (Fox et al, 2017). This system provides an efficient, commercial process for seed production, reducing the labor input required for detasseling.…”
Section: Response To Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…A key requirement for implementation of GMS hybrid production systems is a DNA sequence capable of fully restoring fertility to a line that is male-sterile due to a single locus that is either recessive in inheritance or which can be rendered recessive by inhibition (Fox et al, 2017). Fertile pollen is the result of a complex, conserved developmental process, and disturbance in any of the numerous responsible genes may result in male-sterility that is suitable for exploitation in breeding systems.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first transgenic male sterility system was described (Mariani et al, 1990), many strategies to produce male-sterile plants have been reported,including chemical inducible male sterility systems (Feng et al, 2014;Singh et al, 2010;Venkatesh et al, 2014), transgenic maintainer systems (Chang et al, 2016;Fox et al, 2017;Perez-Prat and van Lookeren Campagne, 2002;Williams, 1995;Wu et al, 2016) and other biotechnology-based systems (Gils et al, 2008;Millwood et al, 2016;Mitsuda et al, 2006). Among them, the strategy of using transgenic maintainer lines to propagate nuclear male-sterile plants is more desirable and reliable.…”
Section: Introductionmentioning
confidence: 99%